Administrative Discretion in the Investigation of Industrial Accidents and Administrative Investigations in Cases of Violations of State Regulatory Requirements for Occupational Health and Safety - A. V. Terekhova (Сибирское юридическое обозрение, 2024)
The participation of the public administration in the investigation of accidents is interconnected with the proceedings on administrative offenses regarding state regulatory requirements for occupational health and safety. In the context of these types of administrative activities, there arise issues related to the application of administrative discretion. In case of no regulation in the legislation of the Russian Federation, discretion is thoroughly investigated in scholarly papers and used by higher courts. In order to protect the rights and interests of citizens and organizations from uncontrolled discretion and ensure law enforcement, it is necessary to establish criteria of discretion, which is implemented by public administration bodies through the adoption of an administrative act. Moreover, the principles of confidence, legal certainty and proportionality are the basis for the legality of actions, their effectiveness and the protection of the constitutional rights of the observees. The purpose of the study is the administrative discretion in the implementation of the procedure for investigation and administrative investigation in cases of violations of state regulatory requirements for occupational health and safety. The paper analyzes the essence of discretion, describes the procedure for investigating industrial accidents in terms of assessing legal certainty and formalization of the procedure, subjective factors influencing the procedure, timing and results of the investigation. The paper also examines the implementation of discretion through the example of administrative investigation into violations of state regulatory requirements for occupational health and safety. The study uses formal legal method, formal logical and dialectical methods. The following conclusions are made: 1) administrative discretion is determined through the categories of "choice" and "freedom" restricted by law; 2) greater legal certainty of the investigation procedure is required; 3) it is necessary to avoid conducting and extending the terms of an administrative investigation with no just cause; 4) it is important to observe proportionality in imposing administrative penalty.